SKEMA PROTEKSI HAK CIPTA UNTUK CITRA WARNA DIGITAL MENGGUNAKAN VISUAL CRYPTOGRAPHY - , SEPTIA RANI, Drs. Agus Harjoko, M.Sc, Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
A copyright protection scheme based on visual cryptography for digital color images is proposed in this work. It is necessary to protect the copyright so that the image is not misused by others. A binary image is used to mark the ownership of the digital image. Unlike most conventional watermarking schemes, the image to be protected is not directly modified by embedding the watermark into it. Visual cryptography technique is used to generate two share images, namely ownership share image and master share image. Firstly, color image is decomposed by it's component color R, G, and B. Then the image features are extracted using Fourier transform, singular value decomposition, and voting. The features of the image are used to generate the master share image, while the ownership share image is formed by using watermark image and image features. To identify the ownership of the image, the watermark can be obtained by stacking the master share image with the ownership share image. Some experiments are carried out to assess the robustness and security performance of the proposed scheme. The results show that the proposed scheme meets the security criteria and robusts against image processing attacks, especially JPEG compression attack. Keywords : copyright protection, watermarking, visual cryptography, color images